Performance increments without audience: paired data from mixed martial arts fighters during COVID-19 (Revista de Artes Marciales Asiáticas, 2020)
During COVID-19, athletes have been forced to compete in the absence of audience. Athletic and cognitive performance have been shown to be both incremented and decremented when competing either with or without audience, something that has been termed ‘social facilitation’. The current study sought to investigate this effect in a naturalistic experiment due to the current pandemic, in a sport in which the effect has never been examined; mixed martial arts (MMA). A performance variable was constructed, and data from 86 fighters who competed during COVID-19 were collected and compared to previous competition history. In total, 586 bouts were analyzed. Data distribution and assumptions were explored in which non-normal distribution was found. Subsequently, a test of marginal homogeneity and a Wilcoxon Signed Ranks test were performed. The results showed that MMA fighters who won their bout without audience displayed poorer performance’s in previous bouts, which were attended by audience. The current study further explores the notion of social facilitation effects and suggests there may be a need to pro-actively incorporate training alternatives that could mitigate performance decrements in fighters who are prone to negative effects due to external stimuli, such as an audience. However, due to the limited observations in the non-audience condition the study results should be interpreted cautiously and considered highly preliminary.